Acúmulo de fitomassa e composição químico-bromatológica da palma forrageira sob adubação mineral em sequeiro - Coutinho, Maria Janiele Ferreira (2014)
This study aimed to evaluate the influence of NPK fertilization on vegetative growth, yield and chemical composition of cactus pear (Opuntia ficus-indica Mill.). The experiment consisted of sixteen combinations of doses of NPK as Plan Puebla II experimental matrix, distributed in a completely randomized design with four replications. Were performed Observations of the growth of the palm morphometric aspects being checked: number of cladodes per plant (NC) , length (BL) , width (CW) , thickness (CE) and cladodes of the area index of the cladodes (IAC) . Further productivity and chemical composition of cactus pear were studied . The productivity of the palm was influenced significantly based on application of different levels of NPK. Except the width morphometric variables (length, thickness, number of cladodes per plant and leaf area index of cladodes ) were not affected significantly . The analysis of variance for crude protein , unlike the dry matter values statistically different. The results of the FDA rate of cactus pear for the different treatments increased while that increased levels of NPK . The amounts of nutrients used in fertilizers promote small changes in production. The addition of NPK promotes increased protein content, which results in improved nutritional quality of the forage palm.